2023
DOI: 10.20944/preprints202302.0136.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fear of COVID-19, Risk Perception and Preventive Behavior in Health Workers: A Cross-Sectional Analysis in Middle-Income Latin American Countries

Abstract: The aim of this study was to estimate the association between fear of COVID-19 and risk perception with preventive behavior in health professionals from three Latin American countries. An analytical cross-sectional study was conducted. Health professionals with on-site care in Colombia, Ecuador, Guatemala, and Peru were surveyed. Information was collected through an online self-report questionnaire. The main variables were preventive behavior as the dependent variable and fear of COVID-19 and risk perception a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…When examining individual RP questions, their highest level of concern was related to the transmission of COVID-19 to family members, friends, and patients. Previous studies have also shown that healthcare workers were more concerned about infecting others, especially family members and loved ones, than about being infected themselves [ 33 , [51] , [52] , [53] ]. Therefore, the government and/or employing organization should provide healthcare workers with essential resources (e.g., masks and hand sanitizers) to protect their families or alternative housing arrangements to prevent transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When examining individual RP questions, their highest level of concern was related to the transmission of COVID-19 to family members, friends, and patients. Previous studies have also shown that healthcare workers were more concerned about infecting others, especially family members and loved ones, than about being infected themselves [ 33 , [51] , [52] , [53] ]. Therefore, the government and/or employing organization should provide healthcare workers with essential resources (e.g., masks and hand sanitizers) to protect their families or alternative housing arrangements to prevent transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, numerous studies have investigated several aspects of COVID-19 RP [ 10 , 11 , [29] , [30] , [31] , [33] , [34] , [35] ]. However, despite the fact that the COVID-19 pandemic created a disastrous scenario in Brazil, placing the country at the top of the ranking of infections and deaths alongside the United States [ 36 ], there is a limited body of research specifically addressing COVID-19 RP in the country.…”
Section: Introductionmentioning
confidence: 99%